Investigating Cognitive Pathways to Psychopathology: Predicting Depression and Posttraumatic Stress Disorder From Early Responses After Assault. - Kleim, B; Ehlers, A; Glucksman, E (2012)
Depression and posttraumatic stress disorder (PTSD) are common after trauma, but it remains unclear what factors determine which disorder a trauma survivor will develop. A prospective longitudinal study of 222 assault survivors assessed candidate predictors derived from cognitive models of depression and PTSD at 2 weeks posttrauma (N = 222), and depression and PTSD symptom severities (N = 183, 82%) and diagnoses at 6 months (N = 205, 92%). Structural equation modeling showed that the depression and PTSD models predicted both depression and PTSD symptom severity, but that the disorder-specific models predicted the respective outcome best (43% for depression, 59% for PTSD symptom severity). Maintaining cognitive variables (hopelessness and self-devaluative thoughts in depression; cognitive responses to intrusive memories and persistent dissociation in PTSD) showed the clearest specific relationships with outcome. Model-derived variables predicted depression and PTSD diagnoses at 6 months over and above what could be predicted from initial diagnoses. Results support the role of cognitive factors in the development of depression and PTSD after trauma, and provide preliminary evidence for some specificity in maintaining cognitive mechanisms.